Numerical simulation of thermal barrier coating in gas turbine combustion chamber liner: a comparative study of YSZ and PSZ - S M Taseen Wahid; Rashidun Nessa Chowdhury; Jurana Monjur; Muammer Din Arif (Materials Research Express)
This study investigates the potential of Yttria-Stabilized Zirconia (YSZ) and Partially Stabilized Zirconia (PSZ) thermal barrier coatings (TBCs) in improving gas turbine performance through a theoretical simulation. Using the finite element method, we compared temperature and thermal flow distributions within YSZ and PSZ coated combustion chambers against an uncoated Ni substrate liner wall. Our results demonstrate significant reductions in outer wall temperature (2.61%–3.54%) and heat flux (0.44%–0.6%) achieved through TBC application. The findings were validated through similar studies, with results aligning closely with established data. These reductions translate to cooler and more efficient engine operation. This comparative analysis not only sheds light on TBC effectiveness but also provides valuable insights for optimizing combustion chamber design. These findings pave the way for the development of next-generation TBC materials and engineering strategies, ultimately leading to enhanced gas turbine performance.